2015
DOI: 10.32007/med.1936/jfacmedbagdad.v57i4.16
|View full text |Cite
|
Sign up to set email alerts
|

Study the Effect of Cardamom Extracts on Lactobacilli in Comparison to Chlorohexidine gluconate and De-ionized water (in vitro study)

Abstract: Background: Various herbal extracts are known to provide therapeutic benefits in the oral cavity when used topically. One of these herbs is cardamom which is a dried fruit of the tall permanent herbaceous plant, have its place in the family Zingiberaceae. Objectives: Test the effect of green and black cardamom extracts on Lactobacilli in comparison to chlorhexidine gluconate 0.2% and de-ionized water. Materials and methods: Dried fruits of green and black cardamom were extracted by using alcohol 70% ethanol. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…On the other hand, Sara.L.Kahil et al in their study on Elettaria cardamomum extract found good antibacterial activity against Lactobacillus, and this was hypothesised because of the essential oil oleoresin present in it (Khalil et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, Sara.L.Kahil et al in their study on Elettaria cardamomum extract found good antibacterial activity against Lactobacillus, and this was hypothesised because of the essential oil oleoresin present in it (Khalil et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Punica granatum and Elettaria cardamomum are both known for their excellent antimicrobial property (Khalil et al, 2015;Kote et al, 2011). Hence, in the current study, Punica granatum and Elettaria cardamomum mediated zinc oxide nanoparticles have been formulated to determine its antimicrobial activity against Lactobacillus.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of feldspar minerals were found in the soils of the study area, which are potassium feldspar (orthoclase and microcline), and their percentages ranged 00-11.5% and 00-7.11%, respectively. For the second type of plagioclase feldspar (albite and anorthite), rates ranged 3% -21.7%, and 0.0 -7.8%, respectively [5]. During their studies to diagnose heavy and light sand minerals for some soils in the south and north of Iraq, the predominance of quartz mineral in all types of soils of the studied sites within the light part of the light sand minerals, and this was attributed to its resistance to weathering processes as well as being inherited from a substance the origin.…”
Section: Introductionmentioning
confidence: 99%